2015
DOI: 10.1134/s0021364015060107
|View full text |Cite
|
Sign up to set email alerts
|

Magnetocaloric effect in Ni50Mn35In15 Heusler alloy in low and high magnetic fields

Abstract: The magnetic and magnetocaloric characteristics of Ni 50 Mn 35 In 15 Heusler alloy are studied in low and high applied magnetic field. At a magnetic field of 14 T, the adiabatic temperature change ΔT ad measured by the sample extraction technique near the martensitic transformation (≈315 K) is as large as 11 K. This value is an order of magnitude larger than the corresponding change measured at 1.6 T. The observed giant values of the magnetocaloric effect could be related to the suppression of antiferromagneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 8 publications
3
9
0
Order By: Relevance
“…This behavior is assumed to be related to the structural changes that occur near T C : the appearance of a less symmetric tetragonal phase (martensite) in an austenite matrix can mean the appearance of an additional phonon relaxation channel and can result in the determined k ph (T) and η(T) dependences. The coexistence of the austenite and martensite phases near T C in an Ni 50 Mn 35 In 15 alloy also follows from the results in [37].…”
Section: Methodssupporting
confidence: 64%
“…This behavior is assumed to be related to the structural changes that occur near T C : the appearance of a less symmetric tetragonal phase (martensite) in an austenite matrix can mean the appearance of an additional phonon relaxation channel and can result in the determined k ph (T) and η(T) dependences. The coexistence of the austenite and martensite phases near T C in an Ni 50 Mn 35 In 15 alloy also follows from the results in [37].…”
Section: Methodssupporting
confidence: 64%
“…Consequently, these materials are attractive candidates for multifunctional devices, where magnetic and structural characteristics may be manipulated by applied magnetic fields. Since, the magnetocaloric effect results from magnetization changes, remarkable MCE values and time dependency of adiabatic temperature changes have already been reported for these alloys [1,[5][6][7][8][9][10][11][12][13][14] and, in Ref. [15],…”
Section: Introductionmentioning
confidence: 99%
“…The T ad of alloys based on Ni 50 Mn 50-x In x with x~15 have been studied in the vicinity of the phase transitions using direct measurements in Ref. [4][5][6][7][8][9][10][11][12][13]. The largest measured changes were T ad = -2 K and 2 K near the martensitic (first order) and ferromagnetic (second order, at T C ) transitions for ∆H = 1.8 T, respectively [7,11].…”
Section: Introductionmentioning
confidence: 99%
“…The bulk sample's indirect measurement shows 14% higher ∆T ad over the direct measurements. This difference is related to the improper use of Maxwell's equations in calculating the MCE of hysteretic materials 41 and heat losses. Also, direct MCE measurement of the nanostructured sample displays 5% less ∆T ad compared to the indirect measurement.…”
Section: Resultsmentioning
confidence: 99%
“…1 The use of Maxwell equations to describe ∆S M in materials that have a first-order phase transition (FOPT) has been questioned as they are only valid at thermal equilibrium. 41 Nevertheless, it has been recently shown that this artifact can be minimized after using appropriate protocol for the measurements. 42,43 Though, when FOPT occurs, results obtained from Maxwell's equations should be taken with caution.…”
Section: Methodsmentioning
confidence: 99%